Negative Work Attitudes and Task Performance: Mediating Role of Knowledge Hiding and Moderating Role of Servant Leadership - Tian, Zailan; Tang, Chao; Akram, Fouzia; Khan, Muhammad Latif; Chuadhry, Muhammad Asif (Frontiers in Psychology, 2022)
The COVID-19 pandemic has caused a global crisis that particularly hit employments across the globe ea. Due to the economic crisis, many small businesses attempted to minimize their expenses by either closing or downsizing. During such organizational situations, the employees face negative workplace attitudes that lead to knowledge hiding. Such knowledge hiding affects task performance badly. A conceptual framework was developed based on servant leadership and conservation of resource theories to moderate the linkage between negative workplace attitudes and knowledge hiding. Through a multi-time, data collection approach, the authors obtained 363 responses from the education sector in china during the COVID-19 pandemic. PROCESS Hayes model 1, model 4 was used for mediation and moderation analysis. Results show that job insecurity, cynicism, and role stress are significant forces behind knowledge hiding behavior. Furthermore, the knowledge hiding behavior adversely affects task performance. Servant leadership shows a buffering effect on knowledge hiding behavior caused by negative workplace attitudes. This is one of the first studies in the South Asian environment to examine the association between employees' negative attitudes and task performance using the knowledge hiding as a mediator and servant leadership as a moderator in Covid 19 scenario. Lastly, the paper concludes with a consideration at its theoretical, practical implication and its future direction.